Mali, Zone Lacustre Household Dataset, 1997-1998 - International Food Policy Research Institute (International Food Policy Research Institute, 2003)
This case study took place in Niafunké in northern Mali where the International Fund for Agricultural Development (IFAD) has an agricultural development project, the "Projet du Développement de la Zone Lacustre". The site was selected in order to represent food security issues in West African semi-arid and arid environments as well as to represent a francophone country. These data consist of a four round survey of 275 households in 10 villages within the Zone Lacustre, collected in 1997 and 1998. In each survey round, men and women were interviewed separately. Each survey covered the household composition, migration, possessions, agricultural production, nonagricultural income, objective and subjective food consumption measures, and nonfood expenditures. Additional questions on poverty perception and nutritional knowledge, practices, and attitudes were asked in the second, third, and fourth round.